Zebrafish FOXP3 is required for the maintenance of immune tolerance. (August 2017) - Sugimoto, Kotaro; Hui, Subhra P.; Sheng, Delicia Z.; Nakayama, Maki; Kikuchi, Kazu
Abstract: Regulatory T (Treg ) cells play a central role in the suppression of excessive immune responses against both self and non-self antigens. The development and function of Treg cells are controlled by a master regulatory gene encoding the forkhead box P3 (FOXP3) protein in mammals. However, little is known regarding the functions of Treg cells and FOXP3 in non-mammalian vertebrates. In this study, we generated mutant zebrafish lacking a functional FOXP3 ortholog, and demonstrated a significant reduction in survival accompanied by a marked increase in inflammatory gene expression, mononuclear cell infiltration, and T cell proliferation in peripheral tissues. Our findings indicate that the zebrafish FOXP3 protein may have an evolutionally conserved role in the control of immune tolerance, illuminating the potential of the zebrafish as a novel model for investigating the development and functions of Treg cells. Highlights: A zebrafish FOXP3 mutant line is established and characterized. FOXP3 mutant zebrafish show increased cytokine production and lymphoproliferation. Zebrafish may be useful as a new vertebrate model for investigating FOXP3 function.